23-year Follow-Up: Maternal-fetal Lead Toxicity from a Retained Bullet - Raymond, Lawrence William (New Frontiers in Medicine and Medical Research Vol. 10, 2021)
The objective of this report is to update the previous one. A mother developed pre-eclampsia at term and delivered an infant with multiple congenital abnormalities which were likely related to the mother’s high blood lead level. This level was due to a bullet lodged in the fourth lumbar vertebra for the previous 15 years. It increased during the third trimester from 31 to 85 micrograms per deciliter. The infant’s cardio-vascular birth defects were surgically repaired and she underwent repeated chelation which reduced her blood lead level to undetectable. Her other birth defects resolved, she completed high school and is in excellent health.